AN ANALYSIS ON WRITING EXERCISES IN ENGLISH TEXTBOOK FOR GRADE SEVEN ENTITLED "WHEN ENGLISH RINGS A BELL" - Wiwin Sulastri Simanungkalit; Kammer Tuahman Sipayung; harpen silitonga (Jurnal Suluh Pendidikan, 2019)
Abstract This study is attempts Analysis on writing Exerciss In English Textbook Entitled “When English Rings a Bell”. The objectives of this research is to know the types of writing exercises in When English Rings a Bell textbook based on 2013 Curriculum. The research is content analysis design. The instrument for collecting data is documentary is taken from English textbook seventh grade students published by kemendikbud. After observing the textbook, matching with the 2013 Curriculum, the types of writing exercises of When English Rings A Bell Textbook the writer found four type there are is (a) Completing texts, (b) writing sentence dealing with grammar, (c) writing short functional text and (d) Developing vocabulary into sentence. The writer found the kinds practice of exercises there are Controlled exercises and Guided exercises, the result is are: arranging scrambled word into good sentences (not found in the textbook), completing texts/sentences (12,50%), writing sentences dealing with grammar (50%), writing short functional texts (18,75%), developing vocabulary into sentences (18,75%) so the types of writing exercises are dominant is writing sentences dealing with grammar (50%). Keywords : An Analysis, Writing Exercises, Textbook, 2013 Curriculum